EFEKVITAS PENERAPAN RESTORATIVE JUSTICE BERDASARKAN VICTIM-ORIENTED PRINCIPLE TERHADAP TINDAK PIDANA PENGANIAYAAN DI KEPOLISIAN - Arya Ilham Ramadhanu (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The prevalence of assault offenses and the limited capacity of the conventional justice system to prevent recidivism underscore the necessity for a more humanistic restorative justice approach. This study aims to examine the effectiveness of implementing victim-oriented principles within restorative justice mechanisms for assault crimes and to assess their influence on reducing recidivism within law enforcement, using a case study of the Pati Police Criminal Investigation Unit. The research employs an empirical legal methodology with a statute approach, utilizing data obtained through interviews and literature review. The findings indicate that the implementation of victim-oriented principles in restorative justice for assault offenses at the Pati Police Criminal Investigation Unit has proven to be effective and consistent with the objectives of substantive justice. Furthermore, this approach demonstrates a significant impact on the reduction of recidivism, as the processes of dialogue and reconciliation foster empathy and moral awareness among offenders, thereby diminishing the likelihood of reoffending.